The Moderation of Human Characteristics in the Control Mechanisms of Rumours in Social Media: The Case of Food Rumours in China - Sun, Sangluo; Ge, Xiaowei; Wen, Xiaowei; Barrio, Fernando; Zhu, Ying; Liu, Jiali (Frontiers in Psychology, 2022)
Social networks are widely used as a fast and ubiquitous information-sharing medium. Mass spread of food rumours has seriously invaded public's healthy life and impacted food production. It can be argued that the government, companies and the media have the responsibility to send true anti-rumour messages in order to reduce panic, the risks involved in different forms of communication to the public have not been properly assessed. The paper develops an empirical analysis model from 683 food anti-rumour cases and 7967 data of the users with top comments to test the influence of the strength of rumour/anti-rumour on rumour control. Furthermore, dividing the users into three categories, Leaders, Chatters, and General Public and study the influence of human characteristics on the relationship between the strength of rumour/anti-rumour and rumour control by considering the different human characteristics as moderator variables. The results showed that anti-rumours have a significant positive impact on the control of rumours; the ambiguity of rumours has a significant negative impact on the Positive Comment Index (PCI) in rumour control. Further, the Leaders increased the overall level of PCI, but negatively adjusted the relationship between evidence and PCI; the Chatters and the General Public reduced the overall level of PCI, and Chatters weakened the relationship between the specific type anti-rumour form and PCI while the General Public enhanced the relationship between the specific type anti-rumour form and PCI. In the long run, the role of Leaders needs to be further improved, and the importance of the General Public is growing in the food rumour control process.